2018
DOI: 10.1021/acs.iecr.8b03586
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biohydrogen Production from Citrus Wastewater Using Anaerobic Sludge Pretreated by an Electroporation Technique

Abstract: Maksudur (2018). Enhanced biohydrogen production from citrus wastewater using anaerobic sludge pretreated by an electroporation technique. Industrial & engineering chemistry research, 58 (2), 573-580.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…It is clearly seen in the FESEM image that EP damaged the microbial cells by creating cleavages on the cell surface during the lipid-extraction process. Similar findings were observed in our previous study, where the higher treatment intensity induced irreversible permeabilization of the cell wall leading to its disruption by triggering pore formation. , A similar observation was reported by Sheng et al, where EP treatment produced a less resistant barrier toward the intrusion of organic solvent; hence, the lipid extraction was enhanced. Thus, the EP technique led to enhanced cell disruption and, subsequently, to a higher lipid yield in the medium.…”
Section: Resultssupporting
confidence: 92%
“…It is clearly seen in the FESEM image that EP damaged the microbial cells by creating cleavages on the cell surface during the lipid-extraction process. Similar findings were observed in our previous study, where the higher treatment intensity induced irreversible permeabilization of the cell wall leading to its disruption by triggering pore formation. , A similar observation was reported by Sheng et al, where EP treatment produced a less resistant barrier toward the intrusion of organic solvent; hence, the lipid extraction was enhanced. Thus, the EP technique led to enhanced cell disruption and, subsequently, to a higher lipid yield in the medium.…”
Section: Resultssupporting
confidence: 92%
“…The authors demonstrated that CWWs showed significantly higher potential for H2 production when compared to synthetic and domestic wastewaters, resulting in a H2 bioconversion efficiency close to 73%. In another study, the hydrogen production from CWWs was maximized by applying an electroporation treatment at different intensity levels (30-120 kWh m -3 ) to achieve methanogen inactivation (Karim et al, 2019).…”
Section: Cwws Anaerobic Treatmentmentioning
confidence: 99%
“…Despite the limited fundamental research for fully understanding the ways that ohmic heating and MEF can assist conventional fermentation methods, it seems that ohmic heating can affect the fermentation process through three main ways (Figure 4). First, electrical treatments can affect the substrates that microorganisms converting to the microbial metabolic products (Gavahian, Munekata, et al, 2019;Karim et al, 2019;Kim et al, 2019).…”
Section: Mechanisms Involved In Mef-and Ohmic-assisted Fermentationsmentioning
confidence: 99%